DFT Study on the Li Mobility in Li-Ion-Based Solid-State Electrolytes. (1st June 2017) - Islam, Md Shafiqul; Simanjuntak, Paul; Mitra, Saibal; Sakidja, Ridwan
ABSTRACT: We have investigated the diffusion mechanisms of Li-ion in amorphous lithium phosphite (LiPO3 ) with the addition of sulphur. By applying the nudge elastic band (NEB) 1 method in crystal LiPO3 and Li3 PO4, we have confirmed the ease in diffusion pathways for Li ions in LiPO3 which is quite consistent with the previous theoretical finding. From our diffusion study in 0.5 Li2 O- 0.5 P2 O5 and 0.4 Li2 SO4 –0.6 (Li2 O-P2 O5 ) melts above 3000K investigated with ab-initio molecular dynamics (AIMD) has been confirmed by experiments at lower temperatures, we have demonstrated the benefit of S addition in increasing the Li + mobility. We have also found that the Li2 SO4 addition into the glass result in a characteristic shift in Li-ion vibration to a lower vibrational frequency. In addition, the presence of oxygen surrounding the diffusion pathways appears to be essential in assisting the Li + mobility in both crystalline and amorphous structures.